2017
DOI: 10.1542/peds.2016-3200
|View full text |Cite|
|
Sign up to set email alerts
|

Decreasing Prescribing Errors During Pediatric Emergencies: A Randomized Simulation Trial

Abstract: A clinical aid providing precalculated medication doses was not associated with a decrease in overall prescribing error rates but was highly associated with a lower risk of 10-fold error for bolus medications and for medications administered by continuous infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
(24 reference statements)
0
17
0
3
Order By: Relevance
“…Multiple studies identify this as a major area where medication errors can occur, and a major contributor to pediatric morbidity and mortality . The weighing of patients only in kilograms is an important safety procedure and many professional organizations including the AAP, ENA, and the Joint Commission have identified this as a national initiative …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies identify this as a major area where medication errors can occur, and a major contributor to pediatric morbidity and mortality . The weighing of patients only in kilograms is an important safety procedure and many professional organizations including the AAP, ENA, and the Joint Commission have identified this as a national initiative …”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39] The weighing of patients only in kilograms is an important safety procedure and many professional organizations including the AAP, ENA, and the Joint Commission have identified this as a national initiative. 40,41 Considering pediatricians and pediatric emergency medicine physicians accounted for less than 10% of staffing in facilities with no significant difference by volume, facilities need systems in place to facilitate identification of ill children. Only 38% of facilities had triage policies that addressed children, and approximately 60% had written policies to notify a physician of abnormal vitals or policies for assessment and reassessment of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized trial in a pediatric ED, the use of a reference book providing weight-based precalculated doses was associated with a lower proportion of prescribing errors for drugs administered by infusion [ 27 ]. The study, however, didn’t look at the preparation errors.…”
Section: Discussionmentioning
confidence: 99%
“…Another study done in the U.S. over one year on 18 pediatric EDs has also shown that the most commonly reported ME were antiinfective agents and analgesics, followed by other medications such as intravenous fluids and respiratory medications [25]. Therefore, clinical aid solutions to assist prescribers with medication prescription (e.g., dose calculators and clinical pharmacists involvement in ED for pediatric patients in the ED) need to be investigated and considered [26].…”
Section: Plos Onementioning
confidence: 99%